Mature cystic teratoma of dorsal spinal cord in adult: An unusual lesion - Kharosekar, Hrushikesh; Naik, Harish; Velho, Vernon (Asian Journal of Neurosurgery, 2018)
Teratomas are a type of multipotential cell tumor that contain a mixture of multiple germinal layers formed by normal organogenesis and reproductive tissues the incidence of intracranial teratomas is low, approximately 0.5-2.2% of all intracranial tumors. The occurrence of teratomas in the spine is extremely rare. Except for in the sacrococcygeal region, teratomas constitute <0.5% of all intraspinal tumors. According to the literature this is only 8th case of dorsal spinal mature cystic teratoma reported till date.
Keywords: Cystic; dorsal spine; mature teratoma